Effect of two aquatic ambient factors (pH and Dissolved Oxygen) on antioxidant generation in skeletal muscle of zebrafish (Danio rerio, Hamilton 1822) - Chowdhury, Sabarna; Saikia, Surjya (Journal of Aquaculture and Fish Health, 2024)
Ambient factors in aquatic body are often responsible for oxidative stress in fish. Zebrafish has been frequently targeted for study to understand such hypoxic effects. In this study, two ambient factors, viz. DO saturation (20-30%, 40-50%, 60-70% and, 80% and above) and pH (4.5-5.5, 5.5-6.5, 6.5-7.5, 7.5-8.5 and 8.5-9.5) were experimented for generation of antioxidant (Catalase, SOD and Glutathione) in the skeletal muscle of zebrafish. The oxidative stress was marked with the levels of MDA in the skeletal muscle. These conditions were tested against the length of treatment period (in hr) from 4hr to 16 hr for each DO saturation level and 1hr to 4 hr for each pH level. The analysis of data shows that, for DO saturation, the skeletal muscle of zebrafish suffered maximum at 12 hr of treatment period having highest level of MDA against 20-30% of saturation level. Similarly, for pH, this period was 2hr and the treatment level was pH 4.5-5.5. Although alkaline ambiance (pH 8.5-9.5) also exerted strong oxidative stress at 2 hr, but it was significantly low in terms of generation of MDA.  In all cases, the antioxidant levels spiked after post maximum generation period i.e. 16 hr for DO saturation and 2 hr for pH level. This indicates a time point wherefrom the fish undergoes oxidative stress and initiation of a counter mechanism during the post oxidative stress period in these two ambient conditions. A two-way ANOVA has explained that the effect of treatment period and the level of ambient factors significantly contributed to the antioxidant generation in zebrafish. The outcome of this work will directly help in management of fish culture when the aquatic body turns to hypoxic or acidic in nature.